2022
DOI: 10.1038/s41598-022-25050-3
|View full text |Cite
|
Sign up to set email alerts
|

Non‑small cell lung cancer carrying PBRM1 mutation suggests an immunologically cold phenotype leading to immunotherapy failure even with high TMB

Abstract: High tumor mutation load (TMB-H, or TMB ≥ 10) has been approved by the U.S. FDA as a biomarker for pembrolizumab treatment of solid tumors, including non‑small cell lung cancer (NSCLC). Patients with cancer who have immunotherapy-resistant gene mutations cannot achieve clinical benefits even in TMB-H. In this study, we aimed to identify gene mutations associated with immunotherapy resistance and further informed mechanisms in NSCLC. A combined cohort of 350 immune checkpoint blockade-treated patients from Memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…There are two studies assessing the relationship between loss of PBRM1 and response to ICI treatment. Results from the two studies consistently supported the notion that deficiency of the PBRM1 subunits might be a negative biomarker for the ICI response [ 118 , 119 ]. Interestingly, results from two reports about the relationship between deficiency of ARID subunits and response to ICI treatment showed that there was a positive correlation with higher median overall survival (MOS) and overall survival (OS) in NSCLC, with mutations of ARID1 accompanying a higher TMB and higher PD-L1 expression [ 115 , 117 ].…”
Section: Outcome Of Ici Treatment For Nsclc With Deficiency Of Swi/snfmentioning
confidence: 56%
See 1 more Smart Citation
“…There are two studies assessing the relationship between loss of PBRM1 and response to ICI treatment. Results from the two studies consistently supported the notion that deficiency of the PBRM1 subunits might be a negative biomarker for the ICI response [ 118 , 119 ]. Interestingly, results from two reports about the relationship between deficiency of ARID subunits and response to ICI treatment showed that there was a positive correlation with higher median overall survival (MOS) and overall survival (OS) in NSCLC, with mutations of ARID1 accompanying a higher TMB and higher PD-L1 expression [ 115 , 117 ].…”
Section: Outcome Of Ici Treatment For Nsclc With Deficiency Of Swi/snfmentioning
confidence: 56%
“…As mentioned above, the elevated EZH2 activity in the tumor cell with the alteration of SWI and SNF subunits suppresses the function of Th1-type chemokines and IFN-g-responsive genes. One possibility is that the uncontrolled PRC2 activity may be partially responsible for the cold immunity in some SWI/SNF-deficient tumors, even though TMB was peculiarly high in some of these tumors [ 118 , 119 ]. Numerous studies have been carried out to test combination therapy to overcome the resistance of immunotherapy.…”
Section: Perspectivesmentioning
confidence: 99%